(untitled) (Research, Society and Development, 2022)
To characterize the antihypertensive therapeutic regimens and their associations, in use by hypertensive patients registered in the Family Health Strategy (FHS) of the pole cities of the macro-regions of the state of in the Pernambuco. This is a descriptive and analytical cross-sectional study carried out on a random sample of hypertensive patients. Of the 334 hypertensive participants in the study, 144 had diabetes. Most (62.27%) lived in Recife and were female (68.56%). The interviewees’ average age was 64.1 ± 13.0 years. More than 50% reported the use of diuretics, with the predominant use of hydrochlorothiazide. This class was the most present in polytherapy, while angiotensin receptor blockers, represented by losartan (34.45%) and angiotensin converting enzyme inhibitors (30.25%) were more used in monotherapy; in Recife a greater use of the latter was observed, while in the interior poles the first was privileged. Polytherapy with two antihypertensive drugs predominated and most associations were consistent with national and international guidelines. Some inappropriate associations were identified, such as an angiotensin-converting enzyme inhibitor with an angiotensin receptor blocker. The study expanded the knowledge of antihypertensive treatment regimens used in primary care in a representative sample of a population with socioeconomic vulnerabilities, in an area where information and observations are still scarce. The confrontation between actual practice and recommendations aims to favor the appropriate choice of pharmacotherapy, knowing that blood pressure control is essential to avoid the occurrence of complications.